Getting Better : Improving Health System Outcomes in Europe and Central Asia - Smith, Owen (Washington, DC: World Bank, 2013)
This report is about how to improve health system outcomes in countries in the Europe and Central Asia (ECA) region. Long-term historical trends indicate substantial room for improvement, especially when ECA's health outcomes are compared to those of the Austria, Belgium, Denmark, Finland, France, Germany, Greece, Ireland, Italy, Luxembourg, the Netherlands, Portugal, Spain, Sweden, and the United Kingdom (EU-15). Instead of catching up with their Western neighbors, many countries in ECA have been falling behind. This report, which explores the development challenge facing health sectors in ECA, identifies three key agendas for achieving more rapid convergence with the world's best-performing health systems: (i) the first is the health agenda, in which the main imperative is to strengthen public health and primary care interventions to help achieve the 'cardiovascular revolution' that has taken place in the west in recent decades; (ii) the second is the financing agenda, in which growing demand for medical care must be satisfied without imposing an undue burden on households, by achieving better financial protection, or on government budgets, by ensuring a more efficient use of resources; and (iii) the third agenda relates to broader institutional arrangements. Here, a few key reform ingredients are identified, each of which is common to most advanced health systems but lacking in many ECA countries.